2012
DOI: 10.1166/jnn.2012.6616
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Substrates on Structural and Optical Properties of Tin Oxide (SnO2) Nanostructures

Abstract: We report on controlling the morphology of tin oxide (SnO2) nanostructures and the study of the effect of surface morphology on structural and optical properties of SnO2 nanostuctures. In present work, Tin oxide (SnO2) nanostructures such as nanowires and nanorods have been grown by thermal evaporation of SnO2 powder. To demonstrate the effect of different substrates on the morphology of grown SnO2 nanostructures, the thermal evaporation of SnO2 powder was carried out on Si and gold catalyzed Si (Au/Si) substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…60 In this facile method, the morphology and properties of nanowires are mainly controlled by growth parameters such as temperature, thickness of the catalyst layer, rate of carrier gas ow, and distance between the source and the substrate. 61 Different types of nanostructures are obtained at different locations on an Au/ alumina substrate. ZnO/SnO 2 nanowires possess a comb-like branched structure in Fig.…”
Section: Carbothermal Chemical Vapor Deposition (Ctcvd)mentioning
confidence: 99%
“…60 In this facile method, the morphology and properties of nanowires are mainly controlled by growth parameters such as temperature, thickness of the catalyst layer, rate of carrier gas ow, and distance between the source and the substrate. 61 Different types of nanostructures are obtained at different locations on an Au/ alumina substrate. ZnO/SnO 2 nanowires possess a comb-like branched structure in Fig.…”
Section: Carbothermal Chemical Vapor Deposition (Ctcvd)mentioning
confidence: 99%
“…Then this vaporized material is condensed to form the desired nanostructure by controlling conditions like substrate amount, temperature, and pressure. [40][41][42][43][44] Researchers are working on various synthesis routes to prepare nanomaterials and nanocomposites for specific applications. For nanocomposite synthesis, factors such as the kinetic energy of the added dopant atom, source to substrate ratio, and metal coating thickness come into play.…”
Section: Synthesis Of Tin Oxide and Tin-oxide-based Nanocompositesmentioning
confidence: 99%
“…Similarly, Choi 81 synthesized metal oxide nanowires for optoelectronics using a vapor-liquid-solid (VLS) growth mechanism. In addition, Johari et al 42 also showed the synthesis of SnO 2 nanowires via a vapor-liquid-solid (VLS) growth mechanism where the metal oxide is grown on Au/Si nanospheres to form a SnO 2 /Au/Si nanocomposite.…”
Section: Synthesis Of Tin Oxide and Tin-oxide-based Nanocompositesmentioning
confidence: 99%
“…Thermal deposition occurs in a tube furnace, where powdered materials are vapor condensed at conditions such as temperature and pressure. [151][152][153] To form nanostructured materials, several steps are followed: (1) formation of evaporant at the source, (2) evaporant transport to the substrate, and (3) condensation onto the substrate to synthesize the desired NMs. 128 To customize the nanostructure, specific parameters are to be considered, such as kinetic energy, flow rate, and scattering of gas.…”
Section: Synthesis Of Nanostructured Snomentioning
confidence: 99%